Menakar Iklan Politik Pemilu 2009 - Tinarbuko, Sumbo (Nirmana, 2009)
Political advertisement is a chamberâ€™s window of a political party. It can connect political parties with the society, electors in particular. None of the political parties, legislative applicants, nor the president and vice president candidates want to win the competition of the general elections 2009 without the use of political advertisements. Such is the importance of the political advertisement in â€œpolitical partiesâ€™ businessâ€ that one of the exclusive parameters of political parties is how much fund is used for the political advertisements talked about.